1996
DOI: 10.1210/jcem.81.6.8964880
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of human corpora lutea during cyclic luteal regression and early pregnancy.

Abstract: To elucidate the role of apoptotic cell death in human corpus luteum (CL) regression, human CL during the menstrual cycle and early pregnancy were isolated and processed for biochemical (radio-labeling) analysis of DNA integrity. Total DNA extracted from human CL of the early luteal phase contained predominantly high mol wt DNA, whereas CL of the midluteal phase exhibited the appearance of DNA cleavage into low mol wt ladders characteristic of apoptosis. Although apoptotic DNA cleavage of human CL significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
51
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 29 publications
2
51
1
Order By: Relevance
“…Thus, apoptosis plays a critical role in regulating the number of oocytes available for ovulation, which influences the length of a women's fertile lifespan and the timing of menopause. Apoptosis is also intimately involved in the constant and cyclical remodelling of the ovary that occurs after ovulation, and is particularly important for the later phase of corpus luteum regression involving structural involution (Juengel et al 1993, Shikone et al 1996, Bowen et al 1999, Goyeneche et al 2006, which occurs after the initial decline of progesterone production. Given the clear importance of apoptosis for germ cell development, folliculogenesis and overall female fertility, much research effort has focussed on identifying and characterising the proteins that regulate this process.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, apoptosis plays a critical role in regulating the number of oocytes available for ovulation, which influences the length of a women's fertile lifespan and the timing of menopause. Apoptosis is also intimately involved in the constant and cyclical remodelling of the ovary that occurs after ovulation, and is particularly important for the later phase of corpus luteum regression involving structural involution (Juengel et al 1993, Shikone et al 1996, Bowen et al 1999, Goyeneche et al 2006, which occurs after the initial decline of progesterone production. Given the clear importance of apoptosis for germ cell development, folliculogenesis and overall female fertility, much research effort has focussed on identifying and characterising the proteins that regulate this process.…”
Section: Introductionmentioning
confidence: 99%
“…The others are eliminated by atresia, a process that has the biological and morphological features of programmed cell death, or apoptosis (3)(4)(5). Moreover, in each reproductive cycle, a new corpus luteum will be formed and the old one will degenerate in a process called luteolysis, which is by nature an apoptotic process (4,6,7).…”
mentioning
confidence: 99%
“…It has been reported that apoptosis is one of the important elements for luteinization and atresia 16, 17, 18. Apoptosis is controlled by the expression of a number of regulatory genes, such as the genes that encode the Bcl‐2 family 19, 20.…”
Section: Introductionmentioning
confidence: 99%